AltitudeOmics: effect of ascent and acclimatization to 5260 m on regional cerebral oxygen delivery. Issue 5 (10th March 2014) - Subudhi, Andrew W.; Fan, Jui‐Lin; Evero, Oghenero; Bourdillon, Nicolas; Kayser, Bengt; Julian, Colleen G.; Lovering, Andrew T.; Roach, Robert C.
<x xml:space="preserve">Abstract</x> New Findings What is the central question of this study? Hypoxia associated with ascent to high altitude may threaten cerebral oxygen delivery. We sought to determine whether there are regional changes in the distribution of cerebral blood flow that might favour oxygen delivery to areas associated with basic homeostatic functions to promote survival in this extreme environment. What is the main finding and its importance? We show evidence of a 'brain‐sparing' effect during acute exposure to high altitude, in which there is a slight increase in relative oxygen delivery to the posterior cerebral circulation. This may serve to support basic regulatory functions associated with the brainstem and hypothalamus. Cerebral hypoxaemia associated with rapid ascent to high altitude can be life threatening; yet, with proper acclimatization, cerebral function can be maintained well enough for humans to thrive. We investigated adjustments in global and regional cerebral oxygen delivery (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg5f92x61z" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />DO2</alternatives>) as 21 healthy volunteers rapidly ascended and acclimatized to 5260 m. Ultrasound indices of cerebral blood flow in internal carotid and vertebral arteries were measured at sea level, upon arrival at 5260 m (ALT1; atmospheric pressure 409 mmHg) and after 16 days of acclimatization (ALT16). Cerebral <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg5f92x632" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />DO2</alternatives> was calculated as the product of arterial oxygen content and flow in each respective artery and summed to estimate global cerebral blood flow. Vascular resistances were calculated as the quotient of mean arterial pressure and respective flows. Global cerebral blood flow increased by ∼70% upon arrival at ALT1 (P < 0.001) and returned to sea‐level values at ALT16 as a result of changes in cerebral vascular resistance. A reciprocal pattern in arterial oxygen content maintained global cerebral <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg5f92x5gm" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />DO2</alternatives> throughout acclimatization, although <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg5f92x5h5" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />DO2</alternatives> to the posterior cerebral circulation was increased by ∼25% at ALT1 (P = 0.032). We conclude that cerebral <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg5f92x5k8" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />DO2</alternatives> is well maintained upon acute exposure and acclimatization to hypoxia, particularly in the posterior and inferior regions of the brain associated with vital homeostatic functions. This tight regulation of cerebral <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg5f92x5mt" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />DO2</alternatives> was achieved through integrated adjustments in local vascular resistances to alter cerebral perfusion during both acute and chronic exposure to hypoxia.